Visual Image of the City in the Representations of Its Citizens: A Study of Krasnodar Residents - Oksana R. Tuchina; Ivan A. Apollonov (Peoples' Friendship University of Russia (RUDN University), 2023)
The visual image of a city is an important factor in the subjective well-being of its residents. The perception of the visual side of the urban environment and its impact on the emotional, cognitive and behavioral characteristics of citizens has been studied by both international and Russian scientists. However, most of them focus on certain aspects of the urban environment. In this regard, of research interest are the citizens' complex impressions about the visual image of their city. The study of the visual image of the city was carried out on the basis of the theory of social representations. The purpose of the work was to examine the social representations (SRs) of the visual image of the city and particularly the visual image of Krasnodar. The sample of the study consisted of respondents permanently residing in Krasnodar ( n = 354). The research methods were associative experiment and P. Vergès' "prototypical analysis", which made it possible to identify the hypothetical structure of SRs, using the frequency and rank of occurrence of the concept. The structure of the respondents' SRs of the visual image of their city, obtained as a result of the study, revealed that the core of the citizens' SRs included the architectural ensemble creating the style of the city and the visual characteristics of a well-planned and organized everyday urban space, whereas tourist-attractive elements of the urban environment were on the periphery of their SRs. The respondents' SRs about the visual image of Krasnodar include, first of all, its centers of attraction, i.e., the historical center of the city and the "new center" (Krasnodar Park), as well as visual signs of comfortable and safe living. In general, the results of the study showed that the idea of the visual image of a city is largely determined by the specifics of an individual's place of permanent residence, the historically established features of the urban environment, its opportunities and problems.